Species composition and abundance of the oribatid fauna (Acari, Oribatida) at two lakes in the Fløyen area, Bergen, Norway - Seniczak, Anna; Solhøy, Torstein; Seniczak, Stanisław; De La Riva-Caballero, Arguitxu (Biological Letters, 2011)
Oribatid communities from the edges of two lakes in the Fløyen area, Bergen, Norway, were compared in June 2005. The lower lake, Blåmansvannet (412 m a.s.l.), is surrounded by spruce forest, while the ‘Higher Lake’ (513 m a.s.l.), is above the tree line. Both lakes have a low pH and their edges are dominated by Sphagnum mosses. The abundance of total mites, as well as of Oribatida, were almost 2-fold higher at the ‘Higher Lake’ (51 510 and 51 160 ind./m2, respectively), while species diversity was lower than at Blåmansvannet. On the shore of Blåmansvannet, the eudominant (20% < D ≤ 40%) species was Trimalaconothrus maior, while Liochthonius peduncularis, Limnozetes ciliatus, and Nanhermannia cf. coronata were dominant (10%< D ≤ 20%). At ‘Higher Lake’, the eudominant species was Limnozetes ciliatus, which reached a 4-fold higher abundance (15 930 ind./m2) than at Blåmansvannet, and dominant species were Liochthonius alpestris, Nanhermannia cf. coronata, and Platynothrus punctatus. At both lakes, juveniles made up about 30% of all oribatids. Four species are new to Norway: Ceratoppia sexpilosa, Liochthonius alpestris, Liochthonius peduncularis, and Trhypochthoniellus longisetus.